2001
DOI: 10.2172/786813
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of Borehole WL-3A through -12 in Support of the Vadose Zone Transport Field Study

Abstract: SummaryThis report presents the results of the fiscal year (FY) 2001 core sampling effort conducted to support the Vadose Zone Transport Field Study (VZTFS). The VZTFS has been conducting a series of controlled near-surface tracer tests at the 299-E24-111 Experiment Test-Well Site (also known as the Sisson and Lu site). The purpose of these tests is to address principal uncertainties affecting the understanding of current contaminant distributions under Hanford waste sites, and to improve the prediction of fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[12] Lithostratigraphy at the S&L site was characterized by drilling using a cone penetrometer and wireline sampling [Last et al, 2001]. The vertical heterogeneity at the S&L site was evaluated by visual inspection of the strata, which were classified into five units, which are labeled B through F [Last et al 2001] and shown in Figure 1b. The hydraulic properties at the core scale were from two sources [Schaap et al, 2003;Khaleel et al, 1995].…”
Section: Sisson and Lu Field Sitementioning
confidence: 99%
“…[12] Lithostratigraphy at the S&L site was characterized by drilling using a cone penetrometer and wireline sampling [Last et al, 2001]. The vertical heterogeneity at the S&L site was evaluated by visual inspection of the strata, which were classified into five units, which are labeled B through F [Last et al 2001] and shown in Figure 1b. The hydraulic properties at the core scale were from two sources [Schaap et al, 2003;Khaleel et al, 1995].…”
Section: Sisson and Lu Field Sitementioning
confidence: 99%